High-Performance Thick Cathode Based on Polyhydroxyalkanoate Binder for Li Metal Batteries - Kang, Dong Hyuk; Park, Minhyuck; Lee, Jeonghun; Kim, Chan Yeol; Park, Jimin; Lee, Youn-Ki; Hyun, Jong Chan; Ha, Son; Kwak, Jin Hwan; Yoon, Juhee; Kim, Hyemin; Kim, Hyun Soo; et al. (Springer Nature, 2024)
Thick cathodes can overcome the low capacity issues, which mostly hamper the performance of the conventional active cathode materials, used in rechargeable Li batteries. However, the typical slurry-based method induces cracking and flaking during the fabrication of thick electrodes. In addition, a significant increase in the charge-transfer resistance and local current overload results in poor rate capabilities and cycling stabilities, thereby limiting electrode thickening. In this study, a synergistic dual-network combination strategy based on a conductive nanofibrillar network (CNN) and a nano-bridging amorphous polyhydroxyalkanoate (aPHA) binder is used to demonstrate the feasibility of constructing a high-performance thick cathode. The CNN and aPHA dual network facilitates the fabrication of a thick cathode (≥？250 μm thickness and？≥？90 wt% active cathode material) by a mass-producible slurry method. The thick cathode exhibited a high rate capability and excellent cycling stability. In addition, the thick cathode and thin Li metal anode pair (Li//t-NCM) exhibited an optimal energy performance, affording high-performance Li metal batteries with a high areal energy of？~？25.3 mW h cm？2, a high volumetric power density of？~？1720 W L？1, and an outstanding specific energy of？~？470 W h kg？1 at only 6 mA h cm？2.